Manual de identidad de marca: Waffles Ana María - Yépez Pérez del Solar, Ana Lucía (2020)
Waffles Ana Maria started in 2008 as a hobby for the owner, Ana Maria Perez del Solar, who made traditional homemade waffles for family and friends. Today, Waffles Ana Maria offers 5 different presentations with 4 different flavors. However, the lack of planification and absence of a graphic guidance, is an obstacle for the brand's recognition and their grow. For this reason, it was made a complete diagnosis of the business: interviews with the owner and best clients, observations during preparation, packaging and delivery, contacted suppliers and a revision of social media content. Finally, the brand manual was constructed with the goal of standardizing and renewing communicative elements, considering the original essence of the brand, to ensure an effective communication.